Arcybiskup Józef Teodorowicz (1864-1938). Hierarcha ormiański - Moskałyk, Jarosław (Poznańskie Studia Teologiczne, 2009)
As a hierarch of the Church, Józef Teodorowicz had a unique capacity for combining his calling to priesthood with a concurrent dedication to social and national ministry. That is why he always strongly advocated an authentic development of autonomy and religious freedom of the Armenian minority and of other national communities in Galicia. He was convinced that only by maintaining the community's distinctiveness and identity can traditional values be truly guarded. Teodorowicz was aware that genuine spiritual and cultural ties in a national community living in diaspora can only be cultivated in an attitude of trust and by setting personal example of worthy conduct. Hence in his pastoral letters and on other occasions he attached such powerful prominence to his deep concern about pouring into the hearts of the faithful the spirit of love and courage so that they could be living carriers of the most profound national traditions.